2005
DOI: 10.1038/sj.sc.3101729
|View full text |Cite
|
Sign up to set email alerts
|

A prospective assessment of mortality in chronic spinal cord injury

Abstract: Study design: Prospective mortality study. Objective: To assess the relationship between comorbid medical conditions and other healthrelated factors to mortality in chronic spinal cord injury (SCI). Setting: Boston, MA, USA. Methods: Between 1994 and 2000, 361 males X1 year after injury completed a respiratory health questionnaire and underwent pulmonary function testing. Cause-specific mortality was assessed over a median of 55.6 months (range 0.33-74.4 months) through 12/31/2000 using the National Death Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
412
1
18

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 562 publications
(437 citation statements)
references
References 28 publications
6
412
1
18
Order By: Relevance
“…This model hypothesizes that both disability factors, such as the presence of impairment or significant restrictions in activity or participation, as well as age-related factors (such as chronological age, age at disability onset, disability inception era and duration of disability), can have direct effects on the development and trajectory of SHCs. The model also hypothesizes that disability and age-related variables can influence the effects of 38,39 Chronic pain 40 Constipation 41 Contractures 27 Deep vein thrombosis/pulmonary embolism 42 Depression 42 Fractures 27 Heterotopic ossification 43 Imobilization hypercalcemia 44 Insomnia/sleep difficulties 37 Kidney stones 18,27 Neurogenic bladder 45 Neurogenic bowel 46 Non-urinary tract infections 27 Obesity 29 Osteoporosis/Bone density loss 15,17,29 Pressure sores 18,41 Restrictive lung disease 47 Septicemia 41 Sexual dysfunction 48,49 Sleep apnea 50 …”
Section: Proposed Definition and Conceptual Model Proposed Definitionmentioning
confidence: 99%
“…This model hypothesizes that both disability factors, such as the presence of impairment or significant restrictions in activity or participation, as well as age-related factors (such as chronological age, age at disability onset, disability inception era and duration of disability), can have direct effects on the development and trajectory of SHCs. The model also hypothesizes that disability and age-related variables can influence the effects of 38,39 Chronic pain 40 Constipation 41 Contractures 27 Deep vein thrombosis/pulmonary embolism 42 Depression 42 Fractures 27 Heterotopic ossification 43 Imobilization hypercalcemia 44 Insomnia/sleep difficulties 37 Kidney stones 18,27 Neurogenic bladder 45 Neurogenic bowel 46 Non-urinary tract infections 27 Obesity 29 Osteoporosis/Bone density loss 15,17,29 Pressure sores 18,41 Restrictive lung disease 47 Septicemia 41 Sexual dysfunction 48,49 Sleep apnea 50 …”
Section: Proposed Definition and Conceptual Model Proposed Definitionmentioning
confidence: 99%
“…It has been suggested that much of the excessive (and early) morbidity and mortality in people with chronic SCI is caused by inactivity related illnesses, such as cardiovascular disease, type II diabetes and osteoporosis. 1 In addition, the loss of fitness and independence associated with physical inactivity significantly impacts quality of life and community participation. 2 These facts highlight the importance of promoting physical activity (PA) to improve health, fitness and overall quality of life within the SCI population.…”
Section: Introductionmentioning
confidence: 99%
“…1 As such, they may experience the same chronic conditions as able-bodied persons. 2 Over the past several decades cardiovascular disease (CVD) has become a leading cause of death in the SCI population. 2 The increase in CVD with aging in individuals with SCI reflects that of able-bodied individuals, though at an accelerated rate, higher prevalence, and earlier onset.…”
Section: Introductionmentioning
confidence: 99%
“…2 Over the past several decades cardiovascular disease (CVD) has become a leading cause of death in the SCI population. 2 The increase in CVD with aging in individuals with SCI reflects that of able-bodied individuals, though at an accelerated rate, higher prevalence, and earlier onset. 3 In recent years, researchers have used pulse wave analysis to show that arterial stiffness is associated with CVD, specifically atherosclerotic burden.…”
Section: Introductionmentioning
confidence: 99%